catena-Poly[[[{5,5′-dimethoxy-2,2′-[ethane-1,2-diylbis(nitrilomethylidyne)]diphenolato}manganese(III)]-μ-acetato] methanol monosolvate] - Gervas E. Assey; Anand M. Butcher; Ray J. Butcher; Yilma Gultneh (Acta Crystallographica Section E, 2010)
The title MnIII compound, {[Mn(C18H18N2O4)(CH3COO)]·CH3OH}n, was synthesized by a reaction between manganese(II) acetate and ethylenebis(4-methoxysalicylaldimine). The structure is made up of bis(4-methoxysalicyldene)ethylenediaminatomanganese(III) units bridged by acetate groups, with Mn—N = 1.9786 (9), Mn—O = 1.8784 (10) and Mn—Oacetate = 2.056 (9) and 2.2571 (9) Å, forming a one dimensional polymer (–Mn–acetate–Mn–acetate–) along [100]. The MnIII atom is in a Jahn–Teller-distorted octahedral environment with cis angles ranging from 81.87 (4) to 96.53 (4)° and trans angles ranging from 166.11 (3) to 173.93 (3)°. The methanol solvent molecule is hydrogen bonded to the phenolate O atom. In addition to this classical hydrogen bond, there are weak C—H...O interactions. The structure was determined from a crystal twinned by pseudo-merohedry.